Autodigestion in Crude Extracts of Soybean Leaves and Isolated Chloroplasts as a Measure of Proteolytic Activity - Ragster, Laverne E. (1981)
Two methods of measuring protein breakdown resulting from self-digestion during incubation in extracts of soybean leaves were examined. The release of free α-amino-nitrogen was measured with ninhydrin, and the disappearance of the large subunit of ribulose bisphosphate carboxylase (RuBPcase) was followed with sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Rates of protein breakdown were measured as a function of temperature, pH, and leaf developmental stage and in the presence of various proteinase inhibitors. These treatments had differential effects on apparent proteolysis, depending on the method used. Determination of the ratio of α-amino-nitrogen plus peptide bond-nitrogen to α-amino-nitrogen indicated that the ninhydrin method detected the activity of exopeptidases preferentially. The disappearance of the large subunit of RuBPCase as shown on gels was due primarily to the activity of endopeptidases. The sensitivity of the two types of proteolytic degradation to proteinase inhibitors differed. Determination of temporal changes in proteolytic activity during leaf development showed that total proteolytic activity, measured by either method, increased during leaf expansion and maturation and decreased during senescence. Incubation of intact isolated chloroplasts at 37 C resulted in the breakdown of the large subunit of RuBPcase, although the chloroplasts contained no measurable proteinase activity as determined by the release of α-amino-nitrogen during the incubation. No acid proteinase (pH 4.5) activity was detected in the chloroplasts when hemoglobin was used as a substrate. These results indicate that the proteinases which break down RuBPCase in isolated chloroplasts may not be detectable by conventional assay procedures.